Pengaruh Persepsi Agen Brilink Terhadap Keputusan Penggunaan Layanan Branchless Banking : The Effect of Agent Brilink Perception on The Decision to Use Branchless Banking Service - Riza Rahmanu; Lilik Noor Yuliati; Bunasor Sanim (School of Business, Bogor Agricultural University (SB-IPB), 2020)
This study aims to analyze the influence of Brilink Agents Perception on the decision to use BRI branchless banking service through the AIDA model. The research method is carried out by modeling the Structural Equation Model (SEM) regarding the relationship between brilink agent perceptions of the relative advantage, risk, trust, usefulness, and security as well as the agent's perception of awareness, interest, desire and action. Data collection techniques were carried out by distributing questionnaires to the community around Brilink agents by cluster random sampling. From these results it can be seen that for the brilink agent user model variables that have a dominant influence are trust, security, usefulness, risk, and relative advantage. As for the non-brilink agent model, the most dominant variables are risk, security, trust, relative advantage and usefulness. The results of using SEM also found that the influence of Brilink Agent's perception of the AIDA variable (awareness, interest, desire, and action) had a greater indirect effect, that is, the brilink Agent's perception variable affected awareness then awareness affected interest, desire, and then action. In addition to knowing the effectiveness of brilink agents, a customer response index value is calculated with the results of the Customer Response Index value at each stage having a value above the minimum value so that it can be said that the brilink agent has a good effectiveness. Keywords: branchless banking, customer response index, structural equation model, AIDA